PERILAKU MEROKOK DI KALANGAN MAHASISWA FAKULTAS ILMU SOSIAL DAN ILMU POLITIK UNIVERSITAS RIAU - Kurniawan, Rendra; Kadarisman, Yoskar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research was conducted at the Faculty of Social and Political Science, University of Riau in order to obtain information on the effect of warning the dangers of smoking to changes in smoking behavior of students. Problems in this study were (1) How motif smoking behavior of students in the Faculty of Social and Political Sciences? (2) What are the perceptions of students in the Faculty of Social and Political Sciences billboard warning against smoking? (3) How much influence billboard warning of smoking on smoking behavior of students in the Faculty of Social and Political Sciences ?. The title of this research is "The Effect of Changes Warning Against Smoking Smoking Behavior among Students in the Faculty of Social and Political Science, University of Riau". This type of research is quantitative descriptive described hereinafter in accordance with the actual situation. The collection of data through observation and direct interview to the respondent. Because students who smoked countless then used a technique sampling using purposive sampling technique is a technique determination of sample with a certain consideration. The number of samples in this study as many as 35 people. The data collected from the research, were processed using a frequency table with a percentage. The results showed that the absence of the effect of warning the dangers of smoking to changes in smoking behavior of students, this is evidenced by the absence of a reduction in the frequency of smoking and the lack of action taken against warning the dangers of smoking by students. Keywords: Change, Behavior, Smoking